Inflammatory bowel disease: The harmful mechanism of experiential avoidance for patients' quality of life - Trindade, Inês A. (2016)
This study aimed to test the effects of inflammatory bowel disease symptomatology and associated medical complications on physical and psychological quality of life and to explore whether these relationships are mediated by experiential avoidance. A total of 200 inflammatory bowel disease patients reported demographic and medical data and completed self-report instruments. Results revealed that the tested model presented an excellent fit, explaining 51 per cent of physical quality of life and 53 per cent of psychological quality of life. Inflammatory bowel disease-associated complications directly impacted on physical quality of life, and experiential avoidance significantly mediated the relationships between inflammatory bowel disease symptomatology and physical and psychological quality of life. These results highlight the importance of implementing psychological interventions for inflammatory bowel disease patients.